Learning the Area of a Circle with Individual Tablets: Transforming Students’ Learning - Kusaka, Satoshi; Takemura, Hiroki (Universitas Ahmad Dahlan, 2025)
This study investigates how the use of ICT tools can enhance students’ conceptual understanding of the area of a circle in a sixth-grade mathematics classroom. A six-lesson unit was designed integrating tools such as GeoGebra, Figma, a digital textbook, and Google Sheets. These tools supported different phases of learning from visual estimation and formula derivation to application and reflection. Students engaged in dynamic and collaborative tasks, which encouraged them to visualize geometric transformations, share strategies, and reflect on their understanding. Analysis of lesson observations and student reflections revealed three key learning outcomes: improved conceptual understanding through visual representations, increased strategic flexibility via peer interaction, and enhanced metacognitive awareness. The study highlights the importance of selecting and sequencing digital tools according to instructional goals, showing that well-orchestrated ICT integration can deepen mathematical thinking and promote active, reflective learning.